Factors Affecting Fraud Prevention: Internal Control, Whistleblowing System and Moral - Cempakasari, Indira; Cris Kuntadi; Dian Rosdiana (Dinasti International Journal of Digital Business Management, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and penomena relationship or influence between variables. This article reviews the factors that influence fraud prevention, namely: Internal Control, Whistle Blowing System and Morale, a literature study of Human Resource Management. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Internal Control affects Fraud Prevention; 2) Whistle Blowing System affects Fraud Prevention; and 3) Moral affects Fraud Prevention.